Congenital Trypanosoma cruzi infection. Efficacy of its monitoring in an urban reference health center in a non-endemic area of Argentina - de Rissio, Ana María (2010)
Congenital transmission (CT) has acquired relevance in Chagas disease (CHD). A cohort of pregnant CHD women (4,355) and their babies were studied in the period 1994-2004. Children were excluded when they had received blood transfusions, or were born or had been in endemic areas; CT rate was 6.1%. Babies were diagnosed between months 1 and 5 in 68.9% of the cases and between months 6 and 12 in 31.1%. In the latter group, parasitemia was detected in 94% and serology in 74.7%. Between months 6 and 9, parasitemia diagnosed 36.2% (P = 0.000) more cases than serology. If serology had been the diagnosis method, those children would have been considered CT free. Taking the overall outcomes, 38.1% of babies were CT free, and 55.8% did not complete the follow-up. Establishing CT as a public health priority and improving first-line health service, congenital CHD coverage could be more efficient in endemic countries.